Large group portrait of teenage girls at Asilomar for a Y-Teens Conference - Crouch, Steve, 1915-1983 (photographer):::Creator::::::::::::
Large group portrait of teenage girls posing in the sand at Asilomar in June 1951 for the Summer Y-Teens conference. Asilomar is in Pacific Grove, California.